Análise fitoquímica de Luehea divaricata (Martius) e Symplocos uniflora (Benth) - e suas potenciais atividades biológicas - Cunha, Sabrina Bassaldua da (2022)
Luehea divaricata (Malvaceae) and Symplocos uniflora (Symplocaceae), better known as “açoita-cavalo” and “sete sangrias”, respectively, are native Brazilian species from pampa biome with few reports in the literature. The phytochemical investigation of the stem bark of L. divaricata (Malvaceae) resulted in the isolation of seven compounds, two of which are friedelin triterpenes and a mixture of α- and β-amyrin, two flavonoids catechin and penta - hydroxyflavane and two steroids, β-sitosterol and glycosylated β-sitosterol. The study of the species Symplocos uniflora led to the isolation of six compounds, including bis(2-ethyl-heptyl) phthalate, lauric acid, benzoic acid, benzoate-2-methyl-heptyl, 4-hydroxy-3-methoxybenzaldehyde and tetradecan-1-ol, these being isolated for the first time in the species. The structures of the isolated metabolites were elucidated through 1H and 13C NMR, one and twodimensional, by melting point, in addition to comparison with standard sample when available and data available in the literature. The extract, fractions and compounds isolated from both species were tested for their biological activities. The antimicrobial activity test was performed using the microdilution plate method and standard strains of different microorganisms were used: four Gram-positive bacteria (Staphylococcus aureus (Sa), Enterococcus faecalis (Ef), Enterococcus ssp (E) and Bacillus subtilis (Bs), and nine Gram-negative bacteria Shigella sonnei (Ss), Escherichia coli (Ec), Salmonella typhimurium (St), Pseudomonas aeroginosa (Pa), Klebsiella pneumoniae (Kp), Morganella morganii (Mm), Salmonella enteritidis (Se ) and Proteus mirabilis (Pm) and nine fungi Candida albicans(Ca), Candida tropicalis (Ct), Candida krusei (Ck), Candida parapslosis (Cp), Cryptococcus neoformans (Cn), Cryptococcus gatti (Cg), Sacharomyces cerivisae (Sc) , Candida glabrata (Cg) and Candida dublienses (Cd) Crude methanolic extract, its fractions and isolated compounds obtained from acid-base and neutral fractionation of the species Luehea divaricata and Symplocos uniflora showed antibacterial activity against Gram-negative bacteria Pseudomonas aeroginosa with (MIC 50 between 15.6- 31.2µg/mL) and for Gram-positive bacteria Bacillus subtilis with (MIC 50) of 50µg/mL, and effective antifungal activity for the tested strains. The basic ethyl acetate and neutral ethyl acetate fractions of the Luehea divaricata species, when tested for their antioxidant capacity, showed promising results with IC50 values, lower than the BHT standard. This study focused on the evaluation of the ability to inhibit the formation of biofilm of the extracts, fractions and isolates were tested against bacteria (Klebsiella pneumoniae) and fungi (Candida krusei, Candida tropicalis, Cryptococcus gatti, Candida glabrata and Cryptococcus neoformans). The antibiofilm activity was relevant for the crude methanolic extract and the acidic ether fraction of L. divaricata, basic acetate and neutral acetate fractions of S. uniflora with inhibition percentage values between 57.10% to 61.00%, while for the The results were significant for the fungal strains tested. Thus, the phytochemical study and pharmacological activities of the compounds identified from the stem bark of L. divaricata and Symplocos uniflora expand the knowledge about chemotaxonomy, as well as justify its use in ethnopharmacology